Design of multi-band filters using parallel connected topology - Cheab, S. (Czech Technical University, 2018)
This paper presents the design of multi-band filters using parallel connected topology. The resonator in each branch is the dual-mode resonator which provides two resonant modes per passband for miniaturization. The coupling values of the resonator are obtained by mapping the filtering function of the dual-mode resonator to the second order Chebyshev polynomial. The control of the filter parameters, such as pass-band bandwidths and band separation, is addressed. Dual-band and triple-band filter prototypes are designed and fabricated to validate the proposed concept. The measured results show good agreement with the simulations. Â© 2009 Radioengineering.